Manajemen Kepala Desa Dalam Meningkatkan Kinerja Perangkat Desa di Kantor Desa Keruak - ayatullah; Nasrullah Nasrullah; Apriatul Nurismaini (Al-Faizi : Jurnal Politik, Hukum dan Bisnis, 2023)
The leadership Agency head village must be capable of increasing performance apparatus village in operating his task of giving service to society. Leadership That its nature specific, typical, and necessary for situations special society, because exists something limitations and advantages specifically in humans. Research objectives This is to know the planning, implementation, and factors obstacle management head village in increasing performance device village in Keruak Village Office Village. Type of research This is a study qualitative descriptive. location study This was done in the Keruak Village Office. The method used in data collection viz Filed research ( study field ) and library research ( study library ). Collection technique with the use of observation, interviews, and documentation. The results of the study are a) planning management head village to increase performance device village namely (1) Doing Socialization to device village to increase performance (2) Interweaving communication with Village Apparatus, (3) Building cooperation between head villages and devices village, (4) and so on. b) implementation management head village in increase performance device village held by planning that has been done set. c) Inhibiting factors implementation Management Village Head in increase performance device village. In facing obstacles to the implementation of existing programs Head Village seeks and finds the right solution in accordance problems faced. Several solutions used by the head village are (1) socialization, meetings, coaching, supervision, discussion, encouragement as well and motivation to Village officials. (2) communication and coordination so that performance is produced more increase (3) coaching, evaluation, socialization, and training to the employees about development source Power For create competent, disciplined and responsible employees answer.